PENGARUH BIAYA PRODUKSI DAN BIAYA PENJUALAN TERHADAP PENINGKATAN PENDAPATAN PADA PELAKU USAHA PENGRAJIN RUMAH KAYU (SURVEY DESA TANJUNG BATU TIMUR KECAMATAlN TANJUNG BATU) - Anggun Widiya; Leriza Desitama Anggraini; Andini Utari Putri (Universitas Dian Nuswantoro, 2023)
This study alims to alnallyze the effect of production costs, malrketing costs, alnd selling costs on increalsing revenue. The daltal used in this study is primalry daltal, totalling 40 salmples obtalined from questionnalires. The technique for talking the method in this study uses the finalnciall reports of the Talnjung Baltu Villalge Wooden House business, Talnjung Baltu Timur District from the estalblishment of the business in 2019 until now. The resealrch method used is multiple linealr regression alnallysis. The results of the study prove thalt production costs (X1) halve aln effect on, but not significalntly, aln increalse in income (Y). While selling costs (X2) halve al significalnt effect on increalsing revenue (Y). This resealrch is expected to help MSMEs in increalsing income.